Kolizej - Ferlinc, Iva (Urbani izziv, 2005)
Last year''s hot topic in the area of architectural and urban planning in Ljubljana has got to be the New Kolizej project. Due to a change in ownership, the decapitated building in the centre of town has become a topic of discussion, pitting conservationists against demolitioners. The problem stems from the many renovations that the Kolizej has received over the years.Since loosing its initial function, which was given to it by architect Withalm and the Ljubljana magistrate, the Kolizej has slowly, but surely, beenfalling apart. For many years now, the building has become a meeting pointfor the socio-economically less privileged. Moreover, with various renovations and additions that have been done over the years, the heritage site has slowly but surely been stripped of its initial purpose. Various design features have disappeared, and a part of the structure has even fallen down due to poor remodelling. As an example of a successful renovation of a cultural heritage site and an outstanding rehabilitation of a city centre, onehas got to look no further than ones neighbour, the Kunsthaus museum in Graz. There one can see old and new architecture adjacent to each other. Perhaps that is the solution, the merger of various interests in one edifice.
Keywords: arhitekturna dediščina; cultural heritage; Kolizej; kulturna dediščina; Ljubljana; prenova